Utilization Of Interactive E-Books With Learning Objectives Orientation & Problem-Based Learning In Science Learning - Sukaria, Muhammad Ikhsan (MACCA : Science-Edu Journal, 2024)
This study aims to develop and test the effectiveness of interactive e-books oriented to learning objectives and based on Problem Based Learning (PBL) in science learning. This interactive e-book is designed to support students in understanding science concepts more deeply through a structured problem-solving approach. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection was done through observation, questionnaire, and learning outcome test. The results showed that the interactive e-book developed had high validity based on the assessment of material experts and media experts. The implementation of this interactive e-book also significantly improved students' concept understanding and problem solving skills compared to conventional learning methods. Therefore, this PBL-based interactive e-book can be used as an effective alternative learning media to improve the quality of science learning in elementary schools. This research makes an important contribution to the development of digital learning media that is innovative and relevant to the needs of education in the digital era.